(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The current study tries to investigate approaches to communication, including dysphemism and euphemisms in political cartoons. Free expression of public opinion and personal, political cartoon humor and got an essential part of the information and data arena. That makes the political cartoons genre more related and remarkable than before. This given cartoon comprises visual and verbal components, making the selection of communication means in the text particularly challenging. That defines the problem of our survey. The paper has investigated political cartoons published in the USA media. Making use of the content analysis method, we chose 174 dysphemisms and euphemisms, split into lexical-semantic classifications. As a consequence, euphemisms are utilized more commonly in political cartoon than dysphemisms, which stemmed from the genre specificity; hence, the ironic impact is attained by the contrast between the visual and verbal components.